2004
DOI: 10.1002/ejoc.200300576
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Transfer Cycloreversion of 2,3‐Diaryloxetanes: Influence of the Substitution and the Photosensitizer on the Regioselectivity

Abstract: The regioselectivity in the oxidative electron-transfer cycloreversion (CR) of 2,3-diaryloxetanes depends on the substitution of the aryl groups and on the nature of the electrontransfer photosensitizer. The reaction occurs with fragmentation of the C2−C3 and C4−O bonds either in the presence of electron-releasing substituents in the 3-aryl groups, or when chloranil is used as photosensitizer. Thus, CR of the methoxysubstituted derivative trans,trans-3-(4-methoxyphenyl)-4-methyl-2-phenyloxetane (1b) results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Thus, after desulfurization, the tight ion pair 2b ·+ and CA ·– affords alkene 2b and CA by ET. This is consistent with the fact that trans ‐4‐methoxystilbene32 and trans ‐anethole18 were stable in the presence of CA upon irradiation.…”
Section: Mechanistic Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, after desulfurization, the tight ion pair 2b ·+ and CA ·– affords alkene 2b and CA by ET. This is consistent with the fact that trans ‐4‐methoxystilbene32 and trans ‐anethole18 were stable in the presence of CA upon irradiation.…”
Section: Mechanistic Discussionsupporting
confidence: 87%
“…CA is a well‐established ET photosensitizer, and the 3 CA ( E red = 2.15 V vs. SCE, in the triplet state) can react at near‐diffusion‐limited rates with a variety of electron donors 14. This compound has been used in PET reactions with small‐ring hydrocarbons,15 aziridines,16 oxiranes,17 and oxetanes 18…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the fate of the geminate radical ion pairs might be influenced by their spin multiplicity, inherited from that of the involved photosensitizer excited state. However, this does not seem to play an important role in the present case, as it has been demonstrated that cycloreversion occurs from the triplet excited state both with (thia)pyrylium ions and with chloranil …”
Section: Discussionmentioning
confidence: 60%
“…A wide variety of model systems have been employed in experimental investigations of the mechanism of 6-4 photolyases. Parallel to the numerous quantum chemical studies that have made important contributions to the understanding of how CPD photolyases function, 6-4 lesions have also been the subject of theoretical computations. ,, To date, however, no extensive investigation of ET-induced repair of 6-4 photoproducts using state-of-the-art quantum chemical methods has been performed. Given the lack of high-level computational data, the aim of the present work is to explore anionic as well as cationic reaction mechanisms for the regeneration of the native Pyrs from both oxetane and azetidine lesions by means of density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%